Spectroscopic ellipsometry studies of an electrochemically synthesized molecularly imprinted polymer for the detection of an aviation biokerosene contaminant - Buffon, E. [UNESP] (2020)
The present work reports the use of spectroscopic ellipsometry to study the properties of molecularly imprinted poly(ortho-phenylenediamine) film. This polymer was electrosynthesized by cyclic voltammetry and applied for the detection of hexahydrofarnesol, which is the main contaminant of aviation biokerosene. Ellipsometry was used to obtain the thickness of the polymeric film and to investigate the optical and dielectric properties of this material. The results obtained showed that the optical properties and dielectric constants of the molecularly imprinted polymer were sensitive to the presence or absence of the hexahydrofarnesol molecule. Detection studies for this molecule showed that the modified electrode responds linearly in two distinct concentration ranges: 5.0 × 10−8 to 1.3 × 10−7 mol L−1 and 3.0 × 10−7 to 1.5 × 10−6 mol L−1, with the first linear range presenting a sensitivity 27.3 times higher than the second range. This is in line with the behavior of the optical properties (refractive index and extinction coefficient) of the polymeric film, which pointed to the presence of a larger number of imprinted cavities in the non-homogeneous part of the polymer. Essentially, this study proved that, apart from measuring film thickness, spectroscopic ellipsometry is a powerful tool for the characterization of molecularly imprinted polymers.